Modulus enhancement of polypropylene by sorbitol nucleating agent in flow field. Issue 2 (27th December 2020) - Iwasaki, Shohei; Inoue, Mitsuko; Takei, Yurie; Nishikawa, Riho; Yamaguchi, Masayuki
Abstract: The rigidity of an injection‐molded isotactic polypropylene (PP) containing 1, 3:2, 4‐bis‐ o ‐(4‐methylbenzylidene)‐D‐sorbitol (MDBS) as a crystal nucleating agent can be enhanced by selection of appropriate processing conditions. A new method by differential scanning calorimetry measurements showed that the dissolution temperature of 0.4 wt.% MDBS in molten PP is around 210°C. When injection molding was performed below the dissolution temperature, for example, 190°C, the molecular orientation of PP was greatly enhanced. Although this is an anomalous condition for the system to expect good transparency, the product obtained showed a high flexural modulus. In contrast, with high‐temperature processing at 240°C, that is, conventional condition, the modulus decreased because of poor molecular orientation. Transmission electron microscopy observation revealed that MDBS fibrils strongly orient to the flow direction under the low‐temperature processing, in which network structure of MDBS fibers is not detected. The oriented MDBS fibers led to a well‐developed shish‐kebab structure, which is responsible for the pronounced rigidity. Abstract : A novel method is proposed to enhance the rigidity of an injection molded polypropylene product containing a sorbitol derivative as a crystal nucleating agent. The low‐temperature‐processing, at which the fibrils of the sorbitol derivative are not dissolved in the molten PP, enhances the molecular orientation greatly by the alignment of fibrils. This simple technique can be widely applicable in industry.